Renal frame count: A measure of renal flow that predicts success of renal artery stenting in hypertensive patients. Issue 2 (21st July 2015) - Naghi, Jesse; Palakodeti, Samhita; Ang, Lawrence; Reeves, Ryan; Patel, Mitul; Mahmud, Ehtisham
Abstract : Objectives: Renal artery (RA) stenting can improve control of hypertension yet predicting clinical response remains difficult. We sought to determine the role of the renal frame count (RFC) (number of angiographic frames for contrast to reach distal renal parenchyma after initial RA opacification) as a predictor of improvement in blood pressure (BP) after RA stenting. Methods: Renal flow was quantified in 68 consecutive patients (age 72.5 ± 9.1 years, 72% male) undergoing RA stenting for refractory hypertension (BP ≥ 140/90 mm Hg despite treatment with two or more antihypertensive medications) by measuring RFC pre‐RA stenting. Significant renal artery stenosis (RAS) was defined as a stenosis ≥ 70% by visual estimation on angiography. Baseline and 6‐month follow‐up BP was recorded. Clinical response was defined by a drop in systolic blood pressure (SBP) >10 mm Hg on the same or fewer number of anti‐hypertensive medications. Results: Patients with RFC > 30 had SBP reduction (43.2 ± 25.7 mm Hg vs. 30.1 ± 31.3 mm Hg, P  = 0.067), diastolic blood pressure reduction (9.1 ± 19.0 vs. −0.2 ± 13.4 mm Hg, P  = 0.02), and mean arterial pressure reduction (23.8 ± 19.4 vs. 11.8 ± 16.1 mm Hg, P  < 0.001) compared to patients with RFC ≤ 30. Furthermore, baseline RFC >30 was associated with a higher rate of clinical response to RA stenting (93.5% vs. 73%, P  = 0.027). Conclusions: RFC can be used as a clinical predictor of response to RA stenting. RFC > 30 was associated with reduction in BP after RA stenting and was predictive of clinical response. RFC provides a useful intraprocedural tool in assessing the severity of RAS and predicts the likelihood of clinical response following RA stenting. © 2015 Wiley Periodicals, Inc.